Speech rehabilitation in post-stroke aphasia using visual illustration of speech articulators: A case report study. (4th March 2021) - Haldin, Célise; Loevenbruck, Hélène; Hueber, Thomas; Marcon, Valérie; Piscicelli, Céline; Perrier, Pascal; Chrispin, Anne; Pérennou, Dominic; Baciu, Monica
ABSTRACT: Recent studies on the remediation of speech disorders suggest that providing visual information of speech articulators may contribute to improve speech production. In this study, we evaluate the effectiveness of an illustration-based rehabilitation method on speech recovery of a patient with non-fluent chronic aphasia. The Ultraspeech-player software allowed visualization by the patient of reference tongue and lip movements recorded using ultrasound and video imaging. This method can improve the patient's awareness of their own lingual and labial movements, which can increase the ability to coordinate and combine articulatory gestures. The effects of this method were assessed by analyzing performance during speech tasks, the phonological processes identified in the errors made during the phoneme repetition task and the acoustic parameters derived from the speech signal. We also evaluated cognitive performance before and after rehabilitation. The integrity of visuospatial ability, short-term and working memory and some executive functions supports the effectiveness of the rehabilitation method. Our results showed that illustration-based rehabilitation technique had a beneficial effect on the patient's speech production, especially for stop and fricative consonants which are targeted (high visibility of speech articulator configurations) by the software, but also on reading abilities. Acoustic parameters indicated an improvement in the distinction between consonant categories: voiced and voiceless stops or alveolar, post-alveolar and labiodental fricatives. However, the patient showed little improvement for vowels. These results confirmed the advantage of using illustration-based rehabilitation technique and the necessity of detailed subjective and objective intra-speaker evaluation in speech production to fully evaluate speech abilities.